Associations of insulin resistance and insulin secretion with bone mineral density and osteoporosis in a general population - Fu, Yi-Hsiu; Liu, Wei-Ju; Lee, Chia-Lin; Wang, Jun-Sing (Frontiers in Endocrinology, 2022)
We investigated the associations of insulin resistance and β-cell secretion with bone mineral density (BMD) and osteoporosis using data from the National Health and Nutrition Examination Survey. Data on BMD assessed using dual-energy x-ray absorptiometry from 5292 participants were analyzed. Insulin resistance and β-cell secretion were assessed using the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) and β-cell function (HOMA-β), respectively. We divided the study population into four groups according to HOMA-IR (<2 vs. ≥ 2) and HOMA-β (<100 vs. ≥ 100). BMD and T score at the lumbar spine, hip joint, and femur were used for analyses. Osteoporosis was defined as a T score ≤ -2.5. Logistic regression analyses were conducted to examine the associations of HOMA-IR and HOMA-β with osteoporosis, and the joint effects of HOMA-IR and HOMA-β on osteoporosis. We found a positive association between HOMA-IR and osteoporosis in participants with a HOMA-β ≥ 100 (OR 8.773, 95% CI 2.160-35.637, p=0.002 at the femoral neck). A negative association between HOMA-β and osteoporosis was noted in those with a HOMA-IR <2 (OR 0.183, 95% CI 0.038-0.882, p=0.034 at the femoral neck). Compared with participants who had HOMA-IR <2 and HOMA-β <100, those with HOMA-IR <2 and HOMA-β ≥ 100 had a lower risk of osteoporosis (OR 0.169, 95% CI 0.038-0.763, p=0.021 at the femoral neck). In conclusion, the association between HOMA-β and BMD/osteoporosis changed as HOMA-IR increased. HOMA-β was negatively associated with osteoporosis when HOMA-IR <2. The association was not significant when HOMA-IR ≥ 2.